The effects of information and communication technologies on informal caregivers of persons living with dementia: A systematic review. Issue 1 (18th December 2018) - Lucero, Robert J.; Fehlberg, Elizabeth A.; Patel, Aditi G.M.; Bjarnardottir, Ragnhildur I.; Williams, Renessa; Lee, Karis; Ansell, Margaret; Bakken, Suzanne; Luchsinger, Jose A.; Mittelman, Mary
Abstract: Introduction: Information and communication technology (ICT) has emerged as promising to support health care consumers, including informal caregivers. This systematic review seeks to evaluate the state of the science of ICT interventions on the health of informal dementia caregivers. Methods: We searched PubMed, CINAHL, Web of Science, and PsycINFO using concepts associated with ICT, dementia, and caregiver. Studies were assessed using the Quality Assessment Tool for Quantitative Studies. Results: We identified 657 full‐text publications. After removal of duplicates and title, abstract, and full‐text screening, the quality of 12 studies was assessed. Studies varied in technology, implementation, results, and intervention evaluation. Discussion: The methodological quality of the ICT intervention studies among dementia family caregivers was moderate to strong, yet outcome measurement was not uniform. The evidence is strongest for various forms of telephone‐based interventions. However, there is a need for research that includes heterogeneous participants based on gender, race, and ethnicity.